Inactivation of γ‐secretases leads to accumulation of substrates and non‐Alzheimer neurodegeneration - Hermien Acx; Lutgarde Serneels; Enrico Radaelli; Serge Muyldermans; Cécile Vincke; Elise Pepermans; Ulrike Müller; Lucía Chávez‐Gutiérrez; Bart De Strooper (EMBO Molecular Medicine)
Abstract γ‐Secretases are a family of intramembrane cleaving aspartyl proteases and important drug targets in Alzheimer's disease. Here, we generated mice deficient for all γ‐secretases in the pyramidal neurons of the postnatal forebrain by deleting the three anterior pharynx defective 1 (Aph1) subunits (Aph1abc cKO Cre+). The mice show progressive cortical atrophy, neuronal loss, and gliosis. Interestingly, this is associated with more than 10‐fold accumulation of membrane‐bound fragments of App, Aplp1, Nrg1, and Dcc, while other known substrates of γ‐secretase such as Aplp2, Lrp1, and Sdc3 accumulate to lesser extents. Despite numerous reports linking neurodegeneration to accumulation of membrane‐bound App fragments, deletion of App expression in the combined Aph1 knockout does not rescue this phenotype. Importantly, knockout of only Aph1a‐ or Aph1bc‐secretases causes limited and differential accumulation of substrates. This was not associated with neurodegeneration. Further development of selective Aph1‐γ‐secretase inhibitors should be considered for treatment of Alzheimer's disease.